An analysis of maslahah's development through al-Ghazali pre and post al-Ghazah periods - Laluddin, Hayatullah; Mohammad, Mohamad Nasran; Mohd Kusrin, Zuliza; Ahmad, Shofian; Nasohah, Zaini; Muda, Mohd Zamro; Mohd Saman, Md Yazid; Muhammad Husni, Ahmad (Medwell Journal, 2012)
The purpose of this study is to trace and analyze the development of maslahah as a dynamic principle of the Islamic jurisprudence of a high methodological significance. To achieve this objective, the researchers undertake an in depth study of jurists discourse on the subject, tracing various stages of its development. Both historical and analytical methods are adopted in this study. The researchers by referring to Muslim jurists’ discourse on maslahah in the context of the development of legal theory, derive the conclusion that maslahah initially was perceived as a notion of consideration of public welfare. However, its use in this sense was on ad hoc basis and lacked consistency. Its elaborate discussion and hence, recognition as a mature technical term materialised during the 5th century of hijrah. This can be observed clearly from the writings of Muslims jurists of pre-al-Ghazali during al-Ghazali and post-al-Ghazali periods including those of al-Ghazali’s writings, himself. However, Al-Shatibi discussion of maslahah within the framework of the theory of the purposes of the law made it of remarkable and profound importance to methodological reconstruction and renewal of Islamic law.